Nurse's manual of laboratory and diagnostic tests - Cavanaugh, Bonita Morrow, 1952- 4 0 16; 1946- Watson, Juanita; 5 (Philadelphia : F.A. Davis, 1999)
A handbook for nurses on laboratory and diagnostic tests, which presents a profile of each procedure and covers reference values, physiology and pathophysiology, indications and contraindications, and nursing care before and after each test.
Rev. ed. of: Nurse's manual of laboratory and diagnostic tests. 2nd ed. / Juanita Watson, Marie S. Jaffe. 1995.
Includes bibliographical references and indexes.
Adult;Adult.
Keywords: 2 -- 0; 6; Diagnosis, Laboratory;Nursing;Diagnosis;Nursing;Laboratory Techniques and Procedures -- Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc.;nurses' instruction;handbooks.; 20; 2